Sri Lanka Child Growth Cohort (SLCGC): a population-based study on growth faltering of children - Abner Daniel; Dhammica Rowel; Upul Senarath; Vithanage Pujitha Wickramasinghe; Shreenika De Silva Weliange; Guwani Liyanage; Yasaswi Niranjala Walpita; Indika Siriwardena; Kunarathinam Partheepan; Suganya Yogeswaran; Hiranya Senani Jayawickrama; Shreenika D S Weliange; et al. (BMJ Open)
Purpose This paper aims to describe the study design and baseline characteristics of the Sri Lanka Child Growth Cohort (SLCGC), which was established to assess the timing, pattern and determinants of growth faltering in infants and young children in Sri Lanka.Participants A retrospective cohort study was conducted among term-born babies (≥37-week gestation), currently aged between 12 and 24 months. A sample of 1875 mother–child pairs were recruited using two-stage stratified cluster sampling method. Data on sociodemographic characteristics, pregnancy care, feeding practices, childhood illnesses and home risk factors were collected through direct interviews with the caregivers. Pregnancy-related data were obtained from the pregnancy record. Birth weight, serial weight and length records and growth pattern were extracted from the Child Health and Development Record. Current weight and length of the children were measured directly.Findings to date The SLCGC serves as a comprehensive cohort study with a countrywide distribution in Sri Lanka, covering the three main residential sectors, namely the urban, rural and estate sectors in equal proportions. The majority of mothers were housewives (76.8%) and aged <35 years (77.9%). The proportions achieved secondary education in mothers and fathers were 69.0% and 63.7%, respectively. Approximately 30% of mothers were overweight or obese, while 15% were underweight on entry to antenatal care. Of the children, 49.2% were girls, 42.5% were the first-born children in their family and 34.2% were born by caesarean section. Mean birth weight was 2917 g (SD 0.406), with the proportion of low birth weight (less than 2500 g) being 13%.Future plans This data enables investigation of the effects of single exposures on child growth, as well as, more complex epidemiological analyses on multiple simultaneous and time-varying exposures. Data will be available for researchers for further analysis. The next wave of assessment is expected to be done after 12 months.